Is visual inspection with acetic acid (VIA) a useful method of finding pre-invasive cervical cancer? - Maliheh Arab; Atefeh Moridi; Ghazaleh Fazli; Robabeh Ghodssi-Ghasemabadi; Maryam Maktabi; Samaneh Saraeian; Mahdie Sanati (Clinical and Experimental Obstetrics & Gynecology)
Purpose of investigation: The prospects for effective cytological screening in the majority of developing countries are limited. This study evaluated visual inspection with acetic acid (VIA) for the diagnosis of CIN 2-3 in case findings. Materials and Methods: In this prospective study, 1437 asymptomatic women were screened using VIA followed by colposcopy-biopsy of all cases. The predictive efficacy of VIA was determined based on pathological confirmation of CIN 2-3 on colposcopy-directed biopsy. Results: In 388 (27%) out of 1437 cases, the VIA was positive. In 31 (2.1%) cases, CIN 2-3 was confirmed on cervical biopsy. The sensitivity, specificity and negative predictive value (NPV) of the VIA were 41.9%, 73.3%, and 98.2%, respectively. Conclusion: The present study confirmed the value of VIA for screening, with sensitivity of 41.9% and NPV of 98.2%. Future studies should determine the best place for VIA testing alongside other types of testing in screening algorithms.